How the United Kingdom benefits from investments in CGIAR research - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
FAO’s The State of Food Security and Nutrition in the World report (FAO et al. 2020) emphasizes the gradually increasing trend of hunger, measured by the prevalence of undernourishment, since 2014. The global reversal in the declining trend in hunger prior to 2014 can be attributed to a number of factors—conflicts, climate-related shocks, biodiversity loss, and economic slowdowns. The scale and pace of the challenges we face in global, regional, national, and local food systems are unprecedented (Fan and Swinnen 2020). More recently, the COVID-19 pandemic has likely added to and exacerbated the existing challenges to feeding the growing global population. The extent of its impact is largely unknown, however. Since this report was prepared, the Russian invasion of Ukraine and the related food crisis have added to these threats to food security. These challenges are widespread and have implications for the entire planet. Thus, combating hunger calls for global collective action and it is in the United Kingdom’s (UK) national interest to continue its decades-long engagement in the global effort to reduce hunger and undernutrition.